Suitability of different growth substrate for mass multiplication of bacterial antagonists - A.K. SOOD, V.K. AMBARDAR* (Indian Phytopathology, 2010)
Nine substrates viz., clay, farmyard manure + sand, biogas slurry, ecomax fermenta, molasses, neem oil cake, saw dust and wheat bran were evaluated for mass multiplication of bacterial antagonists, Pseudomonas fluorescens and Bacillus cereus isolated from the rhizosphere of tomato crop. Proliferation of the antagonists was enumerated on KB medium and correlated with factors like temperature and pH. Out of nine substrates clay F.Y.M. + sand and ecomax supported maximum growth (100×108 cfu/g) of the antagonist after 72 hr. of incubation at 25±10ºC followed by molasses (77.5×106 cfu/ml) and biogas slurry (22.50×106 cfu/ml). Similarly the substrate clay (100×106 cfu/g), FYM + sand (95×106 cfu/g) and ecomax (88×106 cfu/g) supported maximum multiplication of the antagonists. Temperature studies revealed that P. fluorescens and B. cereus did not show growth at 20ºC after 24 hr. of incubation. However, after 48 hr. the colony count was progressively increased with the rise in temperature and maximum growth occurred at 30ºC and decreased at 35ºC. Thus maximum proliferation of the bacterial anatagonists occurred at 30ºC and 7.5 pH.